ON THE CANONICAL FORMATION OF CERTAIN SECOND-ORDER PARTIAL DIFFERENTIAL DIFFERENTIAL EQUATIONS IN A TYPE PRESERVING FIELD - Kokan DPI Department of Mathematics (Researchparks Publishing, 2023)
Describes the canonical representation of some second-order partial differential equations in a type-preserving domain.